2020
DOI: 10.1073/pnas.1918195117
|View full text |Cite
|
Sign up to set email alerts
|

Cellular pathways of calcium transport and concentration toward mineral formation in sea urchin larvae

Abstract: Sea urchin larvae have an endoskeleton consisting of two calcitic spicules. The primary mesenchyme cells (PMCs) are the cells that are responsible for spicule formation. PMCs endocytose sea water from the larval internal body cavity into a network of vacuoles and vesicles, where calcium ions are concentrated until they precipitate in the form of amorphous calcium carbonate (ACC). The mineral is subsequently transferred to the syncytium, where the spicule forms. Using cryo-soft X-ray microscopy we imaged intrac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
69
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(74 citation statements)
references
References 83 publications
3
69
0
2
Order By: Relevance
“…This difference might result from different processing of the vesicle content in these two cell populations. Indeed, previous studies indicated that calcium vesicles in the skeletogenic cells are biologically processed to eliminate the sea water and increase the calcium concentration, while in the non-skeletogenic cells this processing does not occur [ 11 , 14 ]. Together, these findings indicate that the biological regulation of calcium vesicle content is distinct between the skeletogenic and the ectodermal cells which apparently leads to higher calcium vesicle volume in the skeletogenic calcifying cells.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This difference might result from different processing of the vesicle content in these two cell populations. Indeed, previous studies indicated that calcium vesicles in the skeletogenic cells are biologically processed to eliminate the sea water and increase the calcium concentration, while in the non-skeletogenic cells this processing does not occur [ 11 , 14 ]. Together, these findings indicate that the biological regulation of calcium vesicle content is distinct between the skeletogenic and the ectodermal cells which apparently leads to higher calcium vesicle volume in the skeletogenic calcifying cells.…”
Section: Discussionmentioning
confidence: 99%
“…Within the variety of minerals used and phylum specific proteins, a common design of mineral uptake and deposition emerges from various studies: the mineral enters the cells through endocytosis of extracellular fluid [ 11 , 12 ]. The mineral is then concentrated and maintained in an amorphous phase in intracellular vesicles until the vesicles are deposited into a dedicated compartment where crystallization occurs [ 13 , 14 ]. The biomineralization compartment provides a highly regulated environment for crystal nucleation and growth.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations